Diethylstilboestrol exposure does not reduce testosterone production in human fetal testis xenografts. - Rod T Mitchell; Richard M Sharpe; Richard A Anderson; Chris McKinnell; Sheila Macpherson; Lee B Smith; W Hamish B Wallace; Christopher J H Kelnar; Sander van den Driesche (PLoS ONE)
In rodents, in utero exposure to exogenous estrogens including diethylstilboestrol (DES) results in major suppression of steroidogenesis in fetal testes. Whether similar effects occur in the human fetal testis is equivocal. Based on the results of the rodent studies, we hypothesised that exposure of human fetal testes to DES would result in a reduction in testosterone production. We show, using a xenograft approach, that testosterone production is not reduced in human fetal testis following DES exposure. Human fetal testes (15-19 weeks' gestation, n = 6) were xenografted into castrate male nude mice which were then treated for 35 days with vehicle or 100 µg/kg DES three times a week. For comparison, similar treatment was applied to pregnant rats from e13.5-e20.5 and effects on fetal testes evaluated at e21.5. Xenograft testosterone production was assessed by measuring host seminal vesicle (SV) weights as an indirect measure over the entire grafting period, and single measurement of serum testosterone at termination. Human fetal testis xenografts showed similar survival in DES and vehicle-exposed hosts. SV weight (44.3 v 26.6 mg, p = 0.01) was significantly increased in DES compared to vehicle-exposed hosts, respectively, indicating an overall increase in xenograft testosterone production over the grafting period, whilst serum testosterone at termination was unchanged. In contrast intra-testicular testosterone levels were reduced by 89%, in fetal rats exposed to DES. In rats, DES effects are mediated via Estrogen Receptor α (ESR1). We determined ESR1 protein and mRNA expression in human and rat fetal testis. ESR1 was expressed in rat, but not in human, fetal Leydig cells. We conclude that human fetal testis exposure to DES does not impair testosterone production as it does in rats, probably because ESR1 is not expressed in human fetal Leydig cells. This indicates that DES exposure is likely to pose minimal risk to masculinization of the human fetus.